Proposing a context-sensitive model of family supportive supervision for breastfeeding at work from the global South - Mabaso, Prudence Bongekile (School of Management Studies, 2024)
Managing breastfeeding and employment remains a major challenge for working mothers and for the advancement of gender equality across the world. Despite global public health organisations' attempts to encourage workplace support for breastfeeding, progress remains slow particularly in countries with limited state resources. The small but growing body of research on combining breastfeeding and employment typically originates from high-income countries in the global North. Findings and theories from this literature cannot be uncritically imposed on low and middle-income countries (LMICs) in the global South which have distinct sociocultural, economic, and historic contexts. This study advances understanding and theorising of context-sensitive workplace support for breastfeeding by focusing on a specific form of informal support, family supportive supervisor behaviours (FSSB), in the public education sector in South Africa, a middle-income country in the global South. A qualitative research approach was adopted and enabled grounding of the research in the lived realities and material circumstances of working women in the local context. The contribution of the thesis is shown through three papers. The first paper is an exploratory qualitative study to understand practices and challenges related to breastfeeding at work in a public sector context. Thematic analysis of interview data from working mothers (n = 8) and senior managers (n = 4) in two provincial government departments in the Western Cape provided a context-sensitive understanding of breastfeeding at work. The study findings underscored the key role of supervisors in offering relatively low-cost informal support for mothers to better combine breastfeeding and employment. The second paper builds on the concept of informal support from supervisors as key catalysts to advance support for breastfeeding at work among a specific group of public sector employees, teachers. Interview data from teachers who are mothers (n = 13) and principals as their supervisors (n = 14) yielded findings that presented a critical understanding of FSSB for breastfeeding at work in a global South context. The findings from this study extend knowledge by emphasising the importance of contextual factors which affect supervisors' demonstration of, and mothers' accessing FSSB, cautioning against universalising the FSSB construct across diverse contexts. The final conceptual paper contributes to theory building by proposing a context-sensitive model of FSSB for breastfeeding at work from the global South. Sociocultural, economic, and historicalpolitical factors are proposed as important antecedents of FSSB, and interpersonal trust with one's supervisor as a potential moderator of the relationship between the contextual factors and FSSB. Implications for management and workplace policies in LMICs in the global South are presented and recommendations for future research that opens space for diverse ways of knowing are offered. Keywords: Breastfeeding at work, Blended work and family, Family supportive supervisor behaviours, Low and middle-income country context, Global South, Public education sector